Image Processing, Image Analysis and Real-Time Imaging (IPIARTI) Symposium 2014 Symposium on Acoustic, Speech and Signal Processing (SASSP) 2014 - Anon (Universiti Malaysia Perlis (UniMAP), 2014)
Symposium on Acoustic, Speech and Signal Processing (SASSP) 2014 organized by IEEE Signal Processing Society Malaysia Chapter and the School of Computer and Communication Engineering (SCCE) in collaboration with the School of Mechatronic Engineering (SME) on 30th April 2014, Universiti Malaysia Perlis (UniMAP), Pauh Putra Main Campus, Malaysia.